Testing quantum theory on curved spacetime with quantum networks - Johannes Borregaard; Igor Pikovski (Physical Review Research)
Quantum technologies present new opportunities for fundamental tests of nature. One potential application is to probe the interplay between quantum physics and general relativity—a field of physics with no empirical evidence yet. Here we show that quantum networks open a new window to test this interface. We demonstrate how photon mediated entanglement between atomic or atomlike systems can be used to probe time-dilation-induced entanglement and interference modulation. Key are nonlocal measurements between clocks in a gravitational field, which can be achieved either through direct photon interference or by using auxiliary entanglement. The resulting observable depends on the interference between different proper times, and can only be explained if both quantum theory and general relativity are taken into account. The proposed protocol enables clock interferometry on kilometer-scale separations and beyond. Our work thus shows a realistic experimental route for a first test of quantum theory on curved spacetime, opening up new scientific opportunities for quantum networks.